If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(1 + -2x) = 13 + -6x (1 * 5 + -2x * 5) = 13 + -6x (5 + -10x) = 13 + -6x Solving 5 + -10x = 13 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + -10x + 6x = 13 + -6x + 6x Combine like terms: -10x + 6x = -4x 5 + -4x = 13 + -6x + 6x Combine like terms: -6x + 6x = 0 5 + -4x = 13 + 0 5 + -4x = 13 Add '-5' to each side of the equation. 5 + -5 + -4x = 13 + -5 Combine like terms: 5 + -5 = 0 0 + -4x = 13 + -5 -4x = 13 + -5 Combine like terms: 13 + -5 = 8 -4x = 8 Divide each side by '-4'. x = -2 Simplifying x = -2
| 7+4y=29 | | f(x)=ln(4-x) | | -15=x+11 | | 68/25 | | 4x-2y=6xiny | | x(4x-7)=(4x+5)(x-8) | | 11-3n=15 | | -3n-11=5(4n+7) | | .16y+.09(y+8000)=1970 | | 10-5g=60 | | z^2-8z=-12 | | 2cosx=3^(1/2) | | 2(x+5)+9=5(x-1) | | 4x+7y+5xy=3 | | -20(2)(-4)(-3)= | | 7-4n=8 | | (5y+2)(2y+6)= | | 4(-t+3)+6(2t+6)=t+4-5t | | 4(x-3)-6x=-18 | | -Y-22=66 | | 5v-6=-16 | | x-x*.30=40 | | -m-7=-8+1-8m+m | | 5f-6=33.33 | | x+x*.30=40 | | 9(z+2)-4(z-3)=2(z-2)+2(z-3) | | 2*7x+20y-23x+17x-13y+0.50x= | | 7-2n=6 | | 3(t-12)=27t | | 6.1+5.8(x)=x+80.3 | | -2[6-(4b+8)]-4=4(5+b) | | 3(x+4)-x=4x-3(x-2) |